PENGARUH CEKAMAN AIR TERHADAP PERTUMBUHAN DAN PRODUKSI PADA TANAMAN JAMBU MENTE - M. YACUB LUBIS; JOKO PITONO; PASRIL WAHID (Jurnal Penelitian Tanaman Industri, 1999)
Effects of water stress on plant growth and production of cashewTo complete the characteristic tests of prospective numbers of cashew (Anacardium occidentale L). research on the production stability and envi¬ ronmental stress tolerance were conducted. The objectives of the research were to study the effects of the water stress on the growth performance, inflorescent formation, production and quality of cashew. The research activi¬ ties wee caried out at Cimanggu Research Insulation from Apil 1995 to March 1998. The research used factorial randomized block design with 3 replications and 4 plants per pot. The treatments tested were wateing intervals (A) of 2, 4. 8. and 12 days with 9 mm deep of water for each treatments Prospective numbers of cashew (N) namely Pecangakan. Jepara F2-10. Balak¬ risnan B-02. and Silanka S-21. The results obtained 13 months ater gratings or 11 months ater the application showed that water stress and prospective numbers significantly affected the vegetative growth of the plants namely plant height, primary branch number, secondary branch numbers and canopy diameter. Amongst the prospective numbers, Balakrisnan B-02 had lower growth rate compared with Pecangakan. Jepara F2-I0, and Silanka S-21. Water stress significantly affected the formation of inflorescence, which tended to decrease along with the increase of water stress. On the same level of water stress, the inflorenscent formation of Jepara F2-10 was more domi¬ nant than the other numbers. However the proportion of male flowers, hermaprodite, and the ratio ofhermaprodite flowers to total number of flowers wee not significantly affected by water stress. The difference of inflorescent formation of prospective numbers was significant on the formation of the male flowers only, the highest was Srilanka S-21 and the lowest was Jepara F2- 10. The water stress showed significant effect on the number of the pods per tree, production and the protein content of the cashew nuts. The number of pods per tree and the production tended to decrease along with the increase of water stress, while the protein content of the cashew nut tend to increase along with the water stress incease The number of pods and production per tree were highest on Balakisnan B-02 followed by Pecangakan. Jepara F2-10 and Silanka S-21. espectively, where as the highest protein content of Ihe cashew kernel was on Balakrisnan B-02.